2021
DOI: 10.1016/j.marpol.2021.104712
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary assessment of the impact of Covid-19 Pandemic in the small-scale and recreational fisheries of the Canary Islands

Abstract: Covid-19 pandemic has affected worldwide in many different ways. Fisheries around the world are not an exception due to the long-term isolation and the non-activities period suffered. To do an evaluation of its impact on the fishing sectors in the Canary Islands, 87 online and phone questionnaires were carried out between July and September 2020, conducting the interviews to artisanal fishermen, fishmongers, recreational charter boats fishermen and tackle shops along the archipelago. Both, the artisanal and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Fish marketing and price disruptions due to COVID-19 were widely reported across fisheries of all types and scales, affecting actors throughout fish value chains. Notable patterns of marketing disruption include inactivity or reduced fish marketing in tourism-dependent markets in the Canary Islands (Guerra-Marrero et al, 2021), and globalized export markets in diverse locations (Bassett et al, 2021;Grillo-Núñez et al, 2021;Sowman et al, 2021).…”
Section: Fishing and Marketing Activitiesmentioning
confidence: 99%
“…Fish marketing and price disruptions due to COVID-19 were widely reported across fisheries of all types and scales, affecting actors throughout fish value chains. Notable patterns of marketing disruption include inactivity or reduced fish marketing in tourism-dependent markets in the Canary Islands (Guerra-Marrero et al, 2021), and globalized export markets in diverse locations (Bassett et al, 2021;Grillo-Núñez et al, 2021;Sowman et al, 2021).…”
Section: Fishing and Marketing Activitiesmentioning
confidence: 99%
“…Most of the attention paid to the issue of COVID‐19 and fishers has focused on the impact of lockdowns on the falling demand for seafoods, although it is recognized that the economic impact of the pandemic on fishers' lives and day‐to‐day activities has varied by location (Guerra‐Marrero et al., 2021). Some fishers were stranded at sea by the shutdowns and could not, at first, return to dock, others were locally designated essential works and continued to fish.…”
Section: Health Conditions Among Fishersmentioning
confidence: 99%
“…In countries and jurisdictions where recreational angling was allowed to continue in some form (but with some restrictions, such as social distancing; Paradis et al 2021 ), initial angler surveys and licence sales often suggested increased participation rates (e.g. Guerra-Marrero et al 2021 ; Midway et al 2021 ), including first time anglers and anglers resuming after periods of inactivity (Howarth et al 2021 ), and was likely related to recreational angling being considered a COVID-19 safe activity (‘social fishtancing’; Midway et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%